2009
DOI: 10.3847/aer2009024
|View full text |Cite
|
Sign up to set email alerts
|

The Astronomy and Space Science Concept Inventory: Development and Validation of Assessment Instruments Aligned with the K–12 National Science Standards

Abstract: We report on the development of an item test bank and associated instruments based on those K-12 national standards which involve astronomy and space science. Utilizing hundreds of studies in the science education research literature on student misconceptions, we have constructed 211 unique items that measure the degree to which students abandon such ideas for accepted scientific views. Piloted nationally with 7599 students and their 88 teachers spanning grades 5-12, the items reveal a range of interesting res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 46 publications
3
58
1
3
Order By: Relevance
“…However, it also differs noticeably from regular concept inventories in terms of the breadth of content covered in the assessment. Typically, a concept inventory is an assessment designed to probe student understandings of a single topic [19][20][21]. The FCI is such an example that focuses only on the Newtonian concepts of force-one of the many topics that are discussed in mechanics [8].…”
Section: A Content and Construct Of Bemamentioning
confidence: 99%
“…However, it also differs noticeably from regular concept inventories in terms of the breadth of content covered in the assessment. Typically, a concept inventory is an assessment designed to probe student understandings of a single topic [19][20][21]. The FCI is such an example that focuses only on the Newtonian concepts of force-one of the many topics that are discussed in mechanics [8].…”
Section: A Content and Construct Of Bemamentioning
confidence: 99%
“…In this sense, he meant that psychometrically driven items were ones that tapped previously established misconceptions widely held by students and suggested that the multiple-choice distractors offered to students be those that have been established by systematic astronomy education research (Sadler et al, 2010). This philosophical perspective has influenced the development of a generation of assessment instruments in astronomy education and astronomy education research, most particularly the TOAST (Slater, S., 2014).…”
mentioning
confidence: 99%
“…Böylece "Öğretmenlerin alan bilgileri yetersiz olduğunda bu durum öğrencilerine de yansımaktadır" (Alev & Karal, 2013) probleminin çözümünde rol oynayabilecektir. Çünkü yapılan çalışmalar; öğrenciler, öğretmen adayları ve öğretmenlerin Astronomi ve Elektrik konularında eksik ve yetersiz bilgiye hatta kavram yanılgılarına sahip olduklarını vurgulamaktadır (Bektaşlı, 2016;Brunsell & Marcks, 2005;Kaltakçı & Eryılmaz, 2010;Kanlı, 2014;Karal, Alev & Başkan, 2010;Korur, 2015;Küçüközer & Demirci, 2008;Ogan-Bekiroğlu, 2007;Plummer, 2009;Plummer & Maynard, 2014;Sadler et al, 2010;Small & Plummer, 2014;Steinberg & Cormier, 2013;Trumper, 2000;Trundle et al, 2002Trundle et al, , 2006Wilhelm et al, 2007;Ünsal, Güneş & Ergin, 2001). Öğretmenlerin sahip oldukları alan bilgisi kadar, bu süreçte kullandığı öğretim yöntem ve tekniklerinin de önemli büyüktür (Cantrell, Young & Moore, 2003).…”
Section: Tartışma Sonuç Ve öNerilerunclassified